2018
DOI: 10.1155/2018/2197891
|View full text |Cite
|
Sign up to set email alerts
|

The Fe-Zn Isotopic Characteristics and Fractionation Models: Implications for the Genesis of the Zhaxikang Sb-Pb-Zn-Ag Deposit in Southern Tibet

Abstract: The genesis of the Zhaxikang Sb-Pb-Zn-Ag deposit remains controversial. Three different geological environments have been proposed to model mineralization: a hot spring, a magmatic-hydrothermal fluid, and a sedimentary exhalative (SEDEX) overprinted by a hot spring. Here, we present the electron probe microanalysis (EPMA) and Fe-Zn isotopic data (microsampled) of four samples from the first pulse of mineralization that show annular textures to constrain ore genesis. The Zn/Cd ratios from the EPMA data of sphal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 87 publications
0
19
0
Order By: Relevance
“…The ores in Stage 2 exhibit banded (Figure d), massive (Figure e,f), globular (Figure e), and concentric annular (Figure f) textures. Concurrently, previous studies of Zhaxikang deposits also found the disseminated, brecciated, fine‐grained layered and colloform, net‐veined, and Dal Matianite ore textures (Wang et al, ; Wang, Zheng, Mathur, & Wu, ), as well as syndepositional structure and even ancient hydrothermal vent (Zheng et al, ) in the first episode of mineralization. The above characteristics of the ores from the first episode of mineralization in Zhaxikang deposit are similar to those of the ores from Red Dog SEDEX‐type ore district in Alaska, which reveals typical submarine hydrothermal sedimentation (metasomatism) origin.…”
Section: Geological Settingmentioning
confidence: 56%
See 4 more Smart Citations
“…The ores in Stage 2 exhibit banded (Figure d), massive (Figure e,f), globular (Figure e), and concentric annular (Figure f) textures. Concurrently, previous studies of Zhaxikang deposits also found the disseminated, brecciated, fine‐grained layered and colloform, net‐veined, and Dal Matianite ore textures (Wang et al, ; Wang, Zheng, Mathur, & Wu, ), as well as syndepositional structure and even ancient hydrothermal vent (Zheng et al, ) in the first episode of mineralization. The above characteristics of the ores from the first episode of mineralization in Zhaxikang deposit are similar to those of the ores from Red Dog SEDEX‐type ore district in Alaska, which reveals typical submarine hydrothermal sedimentation (metasomatism) origin.…”
Section: Geological Settingmentioning
confidence: 56%
“…Detailed regional settings of NH have been reported in the previous literature (Wang et al, ; Wang, Zheng, Mathur, & Wu, ; Sun et al, ; Zhou et al, ), here is only a brief description. The strata cropping out in NH mainly include the Precambrian Laguigangri Group and a series of Upper Triassic, Jurassic, Lower Cretaceous, and Quaternary sediments (Figure b).…”
Section: Geological Settingmentioning
confidence: 99%
See 3 more Smart Citations